The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1677/joe.0.1700677
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in primary cultures of normal adrenocortical cells

Abstract: Telomerase activity was measured in isolated cells from bovine and human adrenal cortex, in cells in primary culture, in cells in later passages in culture, and in cells genetically modified by expression of hTERT (human telomerase reverse transcriptase). Telomerase activity in freshly isolated bovine adrenocortical cells and in human adrenal cells from donors of various ages (6-79 years) was very low or undetected. However, primary bovine adrenocortical cell cultures were strongly positive for telomerase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Consistent with this scenario, Ras G12V /SV40 TAg-expressing human and bovine adrenocortical cells had very low levels of telomerase activity (ref. 36; Fig. 4).…”
Section: Telomerase Activity and Telomere Length In Rasmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with this scenario, Ras G12V /SV40 TAg-expressing human and bovine adrenocortical cells had very low levels of telomerase activity (ref. 36; Fig. 4).…”
Section: Telomerase Activity and Telomere Length In Rasmentioning
confidence: 94%
“…Antibodies used were as follows: SV40 TAg, mouse monoclonal antibody PAb108 (Santa Cruz Biotechnology, Santa Cruz, CA); and Ras, mouse monoclonal antibody (R02120, Transduction Laboratories, Lexington, KY). Telomerase activity in detergent extracts of cells was assessed by the telomerase repeat amplification protocol (TRAP) assay as described previously (36). Telomere restriction fragment (TRF) analysis was performed as described previously (27), except that DNA fragments were separated by pulse-field gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to normal human cells, normal bovine cells lack telomerase activity and although the telomeres of bovine cells are relatively long and continue to shorten with each cell division, they eventually become non functional and cell divisions ceases. 25 It has been shown that H-Ras and SV40T can transform normal bovine adrenocortical cells into malignant tumors, indicating that telomerase is not essential for tumorigenesis. Therefore, it is more accurate and physiologically relevant to study the roles of oncogenes such as H-Ras, P53 and pRb in the transformation of human and bovine cells in a telomerase deficient background.…”
Section: Discussionmentioning
confidence: 99%
“…We have generated hTERT-modified bovine and human adrenocortical cells (Thomas et al, 2000;Suwa et al, 2001;Yang et al, 2001;Hornsby, 2004). For both bovine and human adrenocortical cells, we find that when culture conditions are optimized, ectopic expression of hTERT appears to be the only requirement for immortalization (Thomas et al, 2000;Yang et al, 2001;Hornsby, 2004).…”
Section: Safety Of Htert-immortalized Cells: Transplantation Of Normamentioning
confidence: 99%